1998
DOI: 10.1021/ja980241v
|View full text |Cite
|
Sign up to set email alerts
|

Soluble Supports Tailored for Organic Synthesis:  Parallel Polymer SynthesisviaSequential Normal/Living Free Radical Processes

Abstract: To expand the availability and solubility range of polymer supports for liquid-phase organic synthesis (LPOS) we have applied a sequence of normal and "living" free radical polymerization to generate a library of block copolymers possessing either block or graft architecture with initiators 1-4 and a diverse set of vinyl monomers 5-9. The structure, molecular weight, and polydispersity (PD) of the individual library members have been determined by size exclusion chromatography (SEC), 1 H and 13 C NMR, and as a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
69
0
1

Year Published

2002
2002
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(70 citation statements)
references
References 74 publications
0
69
0
1
Order By: Relevance
“…The soluble polymer-supported synthesis [23] of small organic molecules is a subject of intense research activity due to their profit from both the advantageous features of homogeneous solution chemistry (high reactivity, lack of diffusion phenomena, analytical simplicity) and of solid-phase methods (ready isolation and easy purification 1. n =~2 (PEG200-Im), 2. n =~6 (PEG400-Im)…”
Section: Introductionmentioning
confidence: 99%
“…The soluble polymer-supported synthesis [23] of small organic molecules is a subject of intense research activity due to their profit from both the advantageous features of homogeneous solution chemistry (high reactivity, lack of diffusion phenomena, analytical simplicity) and of solid-phase methods (ready isolation and easy purification 1. n =~2 (PEG200-Im), 2. n =~6 (PEG400-Im)…”
Section: Introductionmentioning
confidence: 99%
“…Automated parallel controlled radical polymerizations, [17] like nitroxide-mediated polymerization (NMP), [5,18,19] atom transfer radical polymerization (ATRP), [20,21] and RAFT Communication: An automated parallel synthetic approach has been developed for synthesizing polymer libraries by the Macromolecular Design via the Interchange of Xanthates (MADIX) process. The experimental set-up, parallel polymerizations, characterization, and reproducibility tests are detailed.…”
Section: Introductionmentioning
confidence: 99%
“…The resulting size distribution of the polymer beads was reproducible and showed that this parallel approach is useful for the rapid design of polymeric bead supports and to optimize polymerization conditions. A manual parallel free-radical polymerization approach towards new soluble supports for organic synthesis has been described by Janda et al [48] Bifunctional initiators with both an a-nitrilediazene (-N N-) and a 2,2,6,6-tetramethylpiperidine-N-oxyl (TEMPO) group were utilized to synthesize block copolymers, whereby five different monomers were utilized. The a-nitrilediazene was first polymerized at 70 8C with different monomers.…”
Section: Free-radical Polymerizationmentioning
confidence: 99%